Distance learning strategies for weight management utilizing online social networks versus group phone conference call. (5th May 2017) - Willis, Erik A.; Szabo‐Reed, Amanda N.; Ptomey, Lauren T.; Steger, Felicia L.; Honas, Jeffery J.; Al‐Hihi, Eyad M.; Lee, Robert; Lee, Jaehoon; Oh, Youngha; Washburn, Richard A.; Donnelly, Joseph E.
Summary: Objective: The increase in technology and online social networks (OSNs) may present healthcare providers with an innovative modality for delivering weight management programmes that could have an impact on health care at the population level. The objective of this study was to evaluate the feasibility and efficacy of using an OSN to deliver a weight loss programme to inform future, large‐scale trials. Methods: Seventy individuals (age = 47 ± 12.4, minority = 24.3%) with obesity (BMI = 36.2 ± 4.0) completed a 6‐month weight loss intervention and were randomized to either a conference call or OSN delivery group. Weight loss was achieved by reducing energy intake by 500–700 kcal·d −1 below estimated total daily energy expenditure and progressing physical activity to 300 min/week. Behavioural weight loss strategies were delivered weekly throughout the intervention. Results: Conference call and OSN groups produced clinically meaningful weight loss of ≥5% from baseline to 6 months (phone = −6.3 ± 6.4%, OSN = −5.8 ± 6.7%). There was no significant difference in weight change between groups ( p = 0.765). Conclusion: The phone and OSN groups met the American Heart Association/American College of Cardiology/The Obesity Society's Guidelines by reducing baseline weight by 5–10% within 6 months. OSNs appear to be a viable delivery platform for weight loss interventions; however, larger scale adequately powered trials are needed.